Isaac Orobio The Jewish Argument with Dogma and Doubt - Wilke, Carsten (Studies and Texts in Scepticism, 2018)
In philosophical works that circulated as clandestine manuscripts, the Amsterdam physician and polemicist Isaac Orobio de Castro (1617-1687) defended Judaism intermittently against Christianity and Spinoza's critique of religion. His two-front battle recruited rationalism, scepticism, and rabbinic tradition in complex ways. Six historians have newly explored Orobio's context, literary ethos, and reception at the 400th anniversary of his birth.